THE WEDDING NIGHT IN THE WEDDING RITUALS AMONG THE PEOPLES OF DAGESTAN (19th – EARLY 20th CENTURIES) - Musaeva, Majsarat Kamilovna; Solov'eva, Lubov' Timofeevna (History, Archeology and Ethnography of the Caucasus, 2020)
Based on the methodology of ethnological research – processing of field ethnographic material, archival material, scientific works of individual authors on family, marriage and family rites – the paper describes and analyzes a quite sensitive and controversial topic in the traditions of the peoples of Dagestan related to the preservation of female virginity before marriage. The concept of interpreting the values of chastity is considered in the complex of rituals, ideas and beliefs among the Dagestani peoples not only through the prism of such an important family and social event as wedding, but also as an independent object, although closely related to it.Chastity, or the virginity of a girl before marriage is a subject of heated debate in society, since the attitude to it has been transforming from epoch to epoch, from nation to nation. Nonetheless, there is no special study in Dagestan devoted specifically to the rituals associated with the wedding night – the transition of a girl to the status of a woman. The challenge before us is to fill this gap.The first wedding night of the peoples of Dagestan is associated with an extensive set of rituals, which comprises both ancient and folk beliefs about healthy offspring. The successful conclusion of one of the most important milestones of the human life cycle is starting a family. The happiness of women and their status in society depend on the outcome of this night in Dagestan realities not only of the time under study, but also of today.The fact of chastity, proved on the wedding night, is still relevant among the vast majority of the peoples of Dagestan at the present time. Accordingly, some traditional ethnographic ritual nuances will undoubtedly be of interest to the general public.
Keywords: Dagestan; ritual; wedding; female chastity; wedding night; preventive measures.